2023
DOI: 10.47205/plhr.2023(7-iii)44
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Pakistan’s Educational Policy Landscape in Pursuit of Sustainable Development Goal 4: A view of Stakeholders

Hina Faiz

Abstract: This study aimed to qualitatively assess educational policies in Pakistan in the context of achieving Sustainable Development Goal 4 (SDG 4). The research used in-depth interviews with a diverse group of participants, including educators, officials, and stakeholders from both public and private education sectors. A semi-structured interview protocol was designed to investigate legal aspects of inclusion, equitable quality education, and lifelong learning experiences related to SDG-4 in Pakistan. The study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…National Curriculum in 2006 intends to integrate sustainability across different subjects including English Language (Ministry of Education, 2006) but, few studies have been found on sustainability integration in English language education in Pakistan context, Khalil et al (2023) studied syllabus of BS English for incorporation of sustainable development which recommended for reviewing the well-established curriculum to incorporate sustainable development together with 21st-century skills applying content analysis method. Recent studies have been conducted for the integration of sustainability education in English textbooks for grades VIII, IX & X (Jamil, Anwar & Sohail, 2024;Jamil, Nosheen & Saleem, 2024;Jamil, Rasool & Moin, 2024).…”
Section: Literature Reviewmentioning
confidence: 99%
“…National Curriculum in 2006 intends to integrate sustainability across different subjects including English Language (Ministry of Education, 2006) but, few studies have been found on sustainability integration in English language education in Pakistan context, Khalil et al (2023) studied syllabus of BS English for incorporation of sustainable development which recommended for reviewing the well-established curriculum to incorporate sustainable development together with 21st-century skills applying content analysis method. Recent studies have been conducted for the integration of sustainability education in English textbooks for grades VIII, IX & X (Jamil, Anwar & Sohail, 2024;Jamil, Nosheen & Saleem, 2024;Jamil, Rasool & Moin, 2024).…”
Section: Literature Reviewmentioning
confidence: 99%